THE IMPACT OF AI TOOLS (E.G., CHATGPT) ON DEVELOPING STUDENTS’ WRITING SKILLS IN ESL CLASSROOMS IN UZBEKISTAN - Xudayberganova Ro’za Rasul qizi (TADQIQOTLAR, 2026)
This  article  investigates  the  influence  of  Artificial  Intelligence  (AI)  tools, specifically ChatGPT, on the development of writing skills among ESL (English as a Second Language) students in Uzbekistan. The study analyzes how AI tools affect grammatical accuracy, vocabulary acquisition, and structural organization of texts. The findings  indicate  that  while  the  strategic  integration  of  AI  can  enhance  academic performance  and  student  confidence,  it  simultaneously  poses  challenges  related  to academic integrity and the potential decline of critical thinking. The research provides pedagogical recommendations for EFL/ESL instructors in the local context.